Role of cyclooxygenase isoforms in the altered excitatory motor pathways of human colon with diverticular disease. (August 2014) - Fornai, M; Colucci, R; Antonioli, L; Ippolito, C; Segnani, C; Buccianti, P; Marioni, A; Chiarugi, M; Villanacci, V; Bassotti, G; Blandizzi, C; Bernardini, N
<x xml:space="preserve">Abstract</x> Background and Purpose The COX isoforms (COX‐1, COX‐2) regulate human gut motility, although their role under pathological conditions remains unclear. This study examines the effects of COX inhibitors on excitatory motility in colonic tissue from patients with diverticular disease (DD). Experimental Approach Longitudinal muscle preparations, from patients with DD or uncomplicated cancer (controls), were set up in organ baths and connected to isotonic transducers. Indomethacin (COX‐1/COX‐2 inhibitor), SC‐560 (COX‐1 inhibitor) or DFU (COX‐2 inhibitor) were assayed on electrically evoked, neurogenic, cholinergic and tachykininergic contractions, or carbachol‐ and substance P (SP)‐induced myogenic contractions. Distribution and expression of COX isoforms in the neuromuscular compartment were assessed by RT‐PCR, Western blot and immunohistochemical analysis. Key Results In control preparations, neurogenic cholinergic contractions were enhanced by COX inhibitors, whereas tachykininergic responses were blunted. Carbachol‐evoked contractions were increased by indomethacin or SC‐560, but not DFU, whereas all inhibitors reduced SP‐induced motor responses. In preparations from DD patients, COX inhibitors did not affect electrically evoked cholinergic contractions. Both indomethacin and DFU, but not SC‐560, decreased tachykininergic responses. COX inhibitors did not modify carbachol‐evoked motor responses, whereas they counteracted SP‐induced contractions. COX‐1 expression was decreased in myenteric neurons, whereas COX‐2 was enhanced in glial cells and smooth muscle. Conclusions and Implications In control colon, COX‐1 and COX‐2 down‐regulate cholinergic motility, whereas both isoforms enhance tachykininergic motor activity. In the presence of DD, there is a loss of modulation by both COX isoforms on the cholinergic system, whereas COX‐2 displays an enhanced facilitatory control on tachykininergic contractile activity.